The effect of cognitive demand on performance of an executive function task following wild blueberry supplementation in 7 to 10 years old children. Issue 11 (13th October 2017) - Whyte, A. R.; Schafer, G.; Williams, C. M.
Abstract : Previously, cognitive benefits of acute flavonoid interventions with children have primarily been found in memory function. The findings here indicate that flavonoid benefits can be extended to executive function. This is particularly evident where the task is more cognitively demanding. Abstract : The cognitive benefits of acute flavonoid interventions have been well documented, however, research to date has found that, depending on developmental stage, these benefits manifest themselves in different cognitive domains. It is argued that the lack of global cognitive effects following flavonoid intervention may be a result of insufficient task sensitivity for those domains where no benefits are found. In children, executive function is a cognitive domain which has shown little apparent benefit following flavonoid intervention. Here, we describe a Modified Attention Network Task (MANT) designed to vary levels of cognitive demand across trials in order to investigate whether flavonoid related benefits can be shown for executive function when task sensitivity is carefully manipulated. Twenty-one children were recruited to a double blind cross-over study consuming 30 g freeze dried blueberry powder (WBB) or placebo before being tested at 3 hours. Performance in the WBB condition was found to be significantly faster in comparison to placebo particularly on more cognitively demanding incongruent and high load trials. Trials in which a visual cue alerted participants to the imminent appearance of the target also showed better performance following WBB administration. We conclude that WBB administration can enhance executive function during demanding elements of a task, but that the complexity and demand of the task as a whole may be equally important to performance.